Case Report: Challenges of insulin and sulfonylurea dosing in an extremely premature infant for the management of KCNJ11-associated neonatal diabetes mellitus - Perera, Ishan; Jensen, Brooke; Patel, Hirenkumar; Garganta, Melissa (Frontiers in Pediatrics, 2025)
IntroductionNeonatal diabetes mellitus (NDM) is a rare disease, the prevalence of which is 1 in 90,000–160,000 live births, with 31% of all preterm diagnoses linked to monogenic causes. NDM is differentiated into transient, permanent, and syndromic NDM. Furthermore, 40% of patients diagnosed with NDM are responsive to oral sulfonylureas (SUs) due to expressed mutations of the ABCC8 or KCNJ11 genes coding for adenosine triphosphate-sensitive potassium channel (KATP) subunits in pancreatic beta (β) cells. SUs bind to the sulfonylurea receptor 1 subunit, closing the KATP channel and increasing insulin secretion. Although SUs remain the mainstay of NDM treatment, these medications are traditionally only dosed and approved for hyperglycemic control in adults. Current treatment regimens suggest a high dose, 1 mg/kg/day, for patients with KCNJ11 neonatal diabetes.Case descriptionOur male neonate was born at 27 weeks and 1,020 g via emergency cesarean section due to complete placenta previa and maternal hemorrhage following perinatal betamethasone administration. Neonatal resuscitation was required. During resuscitation, the patient was intubated and found to be hyperglycemic. He was subsequently started on Regular Humulin at 0.1 units/kg/dose subcutaneously (SQ) and increased to 0.2 units/kg/dose SQ before transfer to our facility on day of life (DOL) 19. In our neonatal intensive care unit, the patient was transitioned to an insulin drip due to difficulty obtaining and administering the appropriate, but minuscule, SQ insulin doses. Genetic testing was positive for a pathogenic variant c.679G>A (p.Glu227Lys) in KCNJ11; therefore, glyburide was started at 0.1 mg/kg/dose twice a day on DOL 54, resulting in euglycemia. Hyperglycemia recurred after an initial attempt to wean; however, a subsequent wean on DOL 70 was successful in maintaining euglycemia without insulin or glyburide for 48 h prior to discharge on DOL 78.DiscussionThis case report describes the unique and complicated clinical course of a premature neonate with an initially undifferentiated class of NDM requiring a microdose-based approach, i.e., a fraction of a regular dose, to both insulin and SU-based management. This report offers a concise recount of the applied diagnostic and therapeutic procedures while suggesting a decision tree for future NDM management in neonates.